2020
DOI: 10.1038/s41598-020-67106-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant density on yield and Quality of perilla sprouts

Abstract: Growth and nutraceutical quality of perilla sprouts is strongly dependent on planting density. This study explored the influence of planting density on growth, photosynthetic parameters, antioxidant capacity, main secondary metabolites, soluble sugar and soluble protein contents of ready-to-eat sprouts. Planting at a density of 1450 plants m−2 significantly increased yield, improved the activities of antioxidant enzymes SOD and CAT, enhanced the generation of reactive oxygen species, increased the content of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
3
10
0
1
Order By: Relevance
“…An increase in MDA content suggests that lipid peroxidation caused by ROS accumulation has resulted in cellular damage. Our results showed an increase in the MDA concentration of both species in MCM, which may indicate that oxidative stress caused cellular damage and therefore metabolic disorders in these plants (Wu et al, 2020). However, an effective antioxidative system in plants can minimize oxidative stress levels and protect their tissues.…”
Section: Effects Of Mixed Growth On Physiological and Biochemical Resistancementioning
confidence: 58%
See 2 more Smart Citations
“…An increase in MDA content suggests that lipid peroxidation caused by ROS accumulation has resulted in cellular damage. Our results showed an increase in the MDA concentration of both species in MCM, which may indicate that oxidative stress caused cellular damage and therefore metabolic disorders in these plants (Wu et al, 2020). However, an effective antioxidative system in plants can minimize oxidative stress levels and protect their tissues.…”
Section: Effects Of Mixed Growth On Physiological and Biochemical Resistancementioning
confidence: 58%
“…Similarly, POD activity plays an important role in antioxidative protection. We observed that the activities of SOD, CAT, and POD were higher in MCM than in PCF and PMB, suggesting that antioxidative enzymes were mobilized to protect the plant tissue from oxidative damage, which showed that mixed plantations may induce water stress conditions ( Wu et al, 2020 ). In addition, future studies should focus on sap flux density to quantify the water stress of both species in the different mixture conditions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(Wang et al, 2020). Superoxide dismutase (SOD) activity was measured at 560 nm with the nitro blue tetrazolium (NBT) photoreduction method (Wu et al, 2020). Peroxidase (POD) activity was estimated based on the absorbance of guaiacol oxidation at 470 nm while catalase (CAT) activity was measured as the decrease rate in the absorbance of H 2 O 2 (Li et al, 2013).…”
Section: Extraction and Assay Of Lipid Peroxidation Hydrogen Peroxide...mentioning
confidence: 99%
“…To introduce netted melon to the local crop structure of Thua Thien Hue, we investigate and establish the cultivation technique for this fruit to grow under the local climate. Plant density contributes profoundly to absorbing sunlight and weed competitiveness of agronomical crops, affecting the final yield [3]. For instance, 11,111 plants/ha is a recommended density in the spring-summer season in Thai Nguyen province [4], or 25,000-27,000 plants/ha in the dry season and 22,000-25,000 plants/ha in the rainy season in the south of Vietnam [5].…”
Section: Introductionmentioning
confidence: 99%